2006
DOI: 10.1590/1808-1657v73p3572006
|View full text |Cite
|
Sign up to set email alerts
|

Resistência Antimicrobiana Em Salmonella Enterica Subsp. Enterica Sorovar Hadar Isoladas De Carcaças De Frango

Abstract: RESUMO A resistência antimicrobiana é um assunto amplamente estudado em todos os gêneros bacterianos, sobretudo em relação aos responsáveis por zoonoses, como o caso da Salmonella, a qual merece especial atenção, já que pode ser transmitida para os seres humanos. O presente estudo foi conduzido para verificar a ocorrência de resistência a agentes antimicrobianos em 22 cepas de Salmonella Hadar isoladas de carcaças congeladas de frango no Estado do Rio Grande do Sul, no período de maio de 1995 a abril de 1996. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Salmonella enterica serovar Hadar (antigenic formulae 6,8:z 10 :e,n,x) has been isolated from foodstuff, broiler chicken, poultry slaughterhouses, and chicken carcasses [213,216,223]. AMR was observed in amoxicillin, chloramphenicol, nalidixic acid, nitrofurantoin, tetracycline, streptomycin, sulfazotrim, and sulfonamide [213,223].…”
Section: Other Salmonella Serovarsmentioning
confidence: 99%
“…Salmonella enterica serovar Hadar (antigenic formulae 6,8:z 10 :e,n,x) has been isolated from foodstuff, broiler chicken, poultry slaughterhouses, and chicken carcasses [213,216,223]. AMR was observed in amoxicillin, chloramphenicol, nalidixic acid, nitrofurantoin, tetracycline, streptomycin, sulfazotrim, and sulfonamide [213,223].…”
Section: Other Salmonella Serovarsmentioning
confidence: 99%
“…In Bangladesh, 88.89% to 100% erythromycin-resistant E. coli and 87% to 100% erythromycin-resistant Salmonella were observed in human, poultry, and livestock isolates. Kibret [94] and Cardoso et al [95] also noticed 100% resistance to Salmonella against erythromycin in India and Brazil, respectively. Adzitey et al [96] found 86% erythromycin-resistant Salmonella in dairy cattle in Ghana.…”
Section: Resistance To Macrolidesmentioning
confidence: 99%